Implementation of The Supreme Court's Letter In Divorce Cases Due To Domestic Violence Within The Religious Court - Kiljamilawati; Asni; Patimah; Mujahidin, Michra Ananda (Alauddin Law Development Journal (ALDEV), 2025)
This study determines the views of judges at the Sungguminasa Religious Court and the implementation of the Supreme Court Circular (SEMA) No. 3 of 2023 in divorce cases due to Domestic Violence (KDRT). The method used a multidisciplinary approach, namely the normative, legal, and sociological approaches. The results of the study indicate that the Sungguminasa Religious Court responded positively to the issuance of SEMA 3 of 2023 as part of a strategic step to minimize the number of divorce cases in Indonesia. Furthermore, the application several cases where the lawsuit or application was rejected based on considerations that did not meet the constraints of unclear specifications of the type of KDRT, evidence, and the existence of certain emergency conditions that hinder judges in implementing the SEMA.